Self-Regulated Learning through the Integration of Kurikulum Berbasis Cinta (Love-Based Curriculum) in Digital Education: A Conceptual Analysis - Rahmawati, Emma; Al-Awawdeh, Nabil (LP2M Institut Agama Islam Negeri (IAIN) Kediri, 2026)
The development of Self-Regulated Learning (SRL) is a critical requirement in elementary education, particularly in Madrasah Ibtidaiyah, to enable students to independently manage and take responsibility for their learning processes. However, the implementation of SRL in instructional practices has not yet been carried out in a systematic and comprehensive manner, especially when curriculum design and the use of instructional media are developed separately. This article examines efforts to strengthen SRL among Madrasah Ibtidaiyah students through the implementation of a Kurikulum Berbasis Cinta (Love-Based Curriculum) (LBC) integrated with the use of digital learning media. This study employs a qualitative approach using a literature review method, involving an examination of books, scholarly articles, and policy documents related to SRL, the Kurikulum Berbasis Cinta known as KBC (Love-Based Curriculum), and digital learning. The findings indicate that the application of the KBC supported by digital learning media fosters the formation of an inclusive, humanistic, and emotionally safe learning environment, while simultaneously cultivating values of empathy, responsibility, and self-awareness among students. The values embedded in the KBC function as affective and ethical foundations in the self-regulation process, whereas digital learning media serve as facilitative tools that support learning planning, control, and reflection. Therefore, the integration of a KBC and digital learning media contributes to the comprehensive strengthening of Self-Regulated Learning among Madrasah Ibtidaiyah students and offers practical implications for the development of more adaptive, humanistic, and sustainable madrasah learning designs.